2013
DOI: 10.1590/s1517-70762013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Nanocompósitos de matriz epoxídica com reforços produzidos a partir do grafite natural

Abstract: RESUMOO grafite é a fonte mais abundante e de baixo custo para obtenção de grafeno. Para sua produção e aplicação em nanocompósitos em escala industrial, o método de redução do óxido de grafite (OG) tem sido o mais utilizado. A oxidação do grafite promove a introdução de grupos funcionais na sua estrutura lamelar que causam o afastamento dos planos cristalinos do grafite, produzindo assim o OG. Sua redução pode ser realizada tanto por métodos químicos quanto térmicos, a qual remove parcialmente os grupos funci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Figure 3(a) shows the FTIR spectrum of the EPS composite, in which characteristic bands can be identified from cellulose, lignin, epoxy, and catalytic groups. 21–23…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(a) shows the FTIR spectrum of the EPS composite, in which characteristic bands can be identified from cellulose, lignin, epoxy, and catalytic groups. 21–23…”
Section: Resultsmentioning
confidence: 99%
“…In this process, natural graphite (NG) is oxidized by a mixture of acids and oxidizing agents, promoting the oxidation of graphite to graphite oxide (GO), containing oxygenated functional groups. Subsequently, the GO undergoes a thermal expansion and is then converted to graphene by reducing agents [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This region contains epoxy rings indicating the degree of cure of the resin. The smaller the number of rings in that region the greater the degree of cure [7]. Thus, it was observed that the resin was completely cured at the submitted temperature of 80°C/4h.…”
Section: Nanocomposites Characterizationmentioning
confidence: 90%
“…Figure-1a and 1b refer to graphite and Figure 1c and 1d refer to graphene oxide (GO). From Figure 1c, a separation between the graphite layers was observed due to factors such as sonication, which creates separation between the sheets, and also the high oxygen content between the graphene sheets [7,15]. Figure 2 shows the infrared spectra normalized of (a) graphite and (b) graphene oxide (GO) and indicates the presence of oxygenated groups such as hydroxyl (O-H) at 3208 cm -1 [16], carbonyl (C=O) at 1714 cm -1 , carbon double bond (C=C) at 1621 cm -1 [17] and epoxy (CO) at 1372 cm -1 [18] in structure from GO.…”
Section: Graphene Oxide Characterizationmentioning
confidence: 99%
See 1 more Smart Citation